ANALISIS PERBANDINGAN EFISIENSI BANK UMUM KONVENSIONAL DAN BANK UMUM SYARIAH DI INDONESIA DENGAN MENGGUNAKAN METODE DATA ENVELOPMENT ANALYSIS - Amalia Amalia; Meutia Fitri (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2018)
This study aims to analyze the efficiency of Conventional Commercial Bank and Islamic Commercial Bank in Indonesian in 2011-2014. The research type used in analysis quantitative descriptive by balanced panel data method. The target sample of this research is Conventional Commercial Bank and Islamic Commercial Bank in Indonesian, there are 9 Conventional Commercial Bank and 9 Islamic Commercial Bank who fulfill the criteria to be the research objects . The data used in this research is secondary data from annual financial reporting in 2011-2014. Data analysis was performed using Data Envelopment Analysis method to find the value of each bank efficiency, and processing the data using program DEAP version 2.1. The results of this research indicate that the average value efficiency of Islamic Commercial Bank with CRS (0,925) and VRS (0,959)models better than Conventional Commercial Bank with value efficiency CRS (0,921) dan VRS (0,952) models.